Flat sheet metal girders with very thin metal web. Part I, - Wagner, Herbert, 1900-1982 (Technical memorandum (United States. National Advisory Committee for Aeronautics), 1931)
The object of this report was to develop the structural method of sheet metal girders and should for that reason be considered solely from this standpoint. The ensuing methods were based on the assumption of the infinitely low stiffness in bending of the metal web. This simplifies the basis of calculations to such an extent that many questions of great practical importance can be examined which otherwise cannot be included in any analysis of the bending stiffness of the buckled plate. This report refers to such points as the safety in buckling of uprights to the effect of bending flexibility of spars, to spars not set parallel, etc. --